Eficácia de medidas de higiene bucal sobre a microbiota oral potencialmente patogênica para pneumonia aspirativa em idosos residentes em instituições de longa permanência - Aguiar, Maria Cecília Azevedo de (2008)
Aspiratory pneumonia is an important public health problem, due to the high prevalence, high indices of morbidity, mortality, internment and financial costs, especially in institutionalized elderly patients. The objective of this study was to evaluate in vivo buccal hygiene efficacy, using isolated mechanic measures in association with chlorhexidine gluconate, on the oral microbiota potentially pathogenic to the aspiration pneumonia (aerobic bacteria, coagulase-negative staphylococcus and staphylococcus aureus) and the buccal microbiota clinical behavior, by the saburra accumulation analysis in elderly patients resident in longterm care institutions. It was developed an experimental study with 108 patients, divided in two experimental groups (A - mechanical hygiene associated to chlorhexidine gluconate topic application and B - only mechanical hygiene) and a control group, where no intervention was accomplished. At the initial it was evaluated the saburra accumulation and a gauze swab was applied in the oral tissues to carry out the cultures and bacterial identification by pattern-proceedings. In the next day, it was begun an intervention in groups A and B with a daily rate along 15 days. It was accomplished new evaluations, repeated at each 15 days without any intervention. It was carried out descriptive and analytic statistical analysis, with 5% significance level and 95% confidence interval. In the end of the hygiene measures, previously accomplished in groups A and B, revealed similar results when compared to results of group C, showing statistical efficacy in occurrence saburra reduction (frequencies A, B and C, were 33,3% x 22,6% x 90%, respectively, p<0,001), in aerobes total count (medians in A, B and C were 2,45 x 2,17 x 3,6, respectively, p=0,005). By 15 days after the end of the treatment, these variables returned to values near initial levels. However, the intervention did not reveal anti-microbial efficacy on S. aureus. Considering the above, there are not sufficient evidences to indicate the chlorhexidine gluconate use in buccal hygiene practices to aspiration pneumonia prevention in elderly patients resident in long-term care institutions, and mechanical measures should be suggested in these cases.